2019
DOI: 10.1111/ecin.12844
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Uncertainty, Fan Travel, and Aggregate Attendance

Abstract: The uncertainty of outcome hypothesis (UOH) informs economists' understanding of consumer decisions to attend sporting events and team revenue generation. We develop a model of fan behavior based on standard expected utility methods which incorporates fan heterogeneity in terms of decisions to travel to away games and strong preferences for wins. The model reflects aggregate attendance outcomes across local and visiting fans, generates predictions consistent with the UOH, and gives rise to concave league‐wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…These findings show that sports fans are affected by the presence of high-performing, conspicuous, and/or distinguished athletic prowess. Matchday characteristics, such as the day of the match (Buraimo & Simmons, 2008; Forrest & Simmons, 2006), the timing of the event (Krumer, 2020), and the geographical distance between competing teams (Humphreys & Miceli, 2020; Wooten, 2018), are commonly used as determinants of sports demand. These studies revealed that weekend matches or post work-hour matches would enjoy increased attendance.…”
Section: Contextual and Theoretical Backgroundmentioning
confidence: 99%
“…These findings show that sports fans are affected by the presence of high-performing, conspicuous, and/or distinguished athletic prowess. Matchday characteristics, such as the day of the match (Buraimo & Simmons, 2008; Forrest & Simmons, 2006), the timing of the event (Krumer, 2020), and the geographical distance between competing teams (Humphreys & Miceli, 2020; Wooten, 2018), are commonly used as determinants of sports demand. These studies revealed that weekend matches or post work-hour matches would enjoy increased attendance.…”
Section: Contextual and Theoretical Backgroundmentioning
confidence: 99%
“…To capture the curvilinear nature of the effect of predicted outcome uncertainty on attendance, we also included the squared term of PS in the model ( PS 2 ). Although some researchers have applied an additional step to calculate winning probabilities from betting odds (e.g., Kuypers, 2000; Paul et al, 2021; Sung & Mills, 2018), we relied on PS (e.g., Brown & Salaga, 2018; Coates & Humphreys, 2010; Humphreys & Miceli, 2020) for three reasons. First, our study focused on basketball.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the number of all-star players on the home ( HAS ) and away ( AAS ) teams in the previous season was included. Star players have been found to influence consumer demand in the NBA (Hausman & Leonard, 1997; Humphreys & Miceli, 2020), Bundesliga (Feddersen & Rott, 2011), and MLS (Sung & Mills, 2018). Third, the Euclidian distance between the home and away teams’ cities (Distance) was measured based on Google Maps and included in our model because visiting-team fans’ travel costs affect their interest in attending a game (Humphreys & Miceli, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g.,Falls & Natke, 2014Humphreys & Miceli, 2020). Travel cost for a specific season is measured by the national real per-mile fuel cost of driving a private automobile.…”
mentioning
confidence: 99%